Severe encephalopathy associated with SARS-CoV-2 Omicron BA.1 variant infection in a neonate - Tetsuhara, Kenichi; Akamine, Satoshi; Matsubara, Yoshie; Fujii, Shunsuke; Kashimada, Wataru; Marutani, Kentaro; Torio, Michiko; Morooka, Yuya; Hanaoka, Nozomu; Fujimoto, Tsuguto; Nakamura-Miwa, Haruna; Arai, Satoru; et al. (Brain & development (Tokyo. 1979), 2022)
The coronavirus disease 2019 (COVID-19), including the Omicron variant, is less severe in children than in adults. To date, there has been no detailed description of COVID-19-associated severe encephalopathy due to the Omicron variant during the neonatal and early infantile periods. During the outbreak of the Omicron variant, a 29-day-old male presented with a pale and ill appearance. The patient was intubated for mechanical ventilation owing to recurrent apnea, which subsequently turned out to be a breath-holding that may have been caused by seizure. In addition, nonconvulsive status epilepticus was observed. Total duration of repetitive seizure activities was approximately 30 min per hour when seizures were most severe. Brain magnetic resonance imaging (MRI) on day 14 revealed extensive hyperintensity in the T2 sequence, hypointensity in the fluid-attenuated inversion recovery (FLAIR) sequence in the deep and subcortical white matter, and diffusion restriction in the corpus callosum. The Omicron BA.1 variant of the severe acute respiratory syndrome coronavirus 2 was detected in his respiratory sample. Follow-up MRI on day 45 revealed multiple cystic cavitations. Although COVID-19 is not severe in most children, life-threatening conditions such as COVID-19-associated severe encephalopathy can occur during the neonatal and early infantile periods.